Towards a Global Solvency Model in the Insurance Market: A Qualitative Analysis - Garayeta-Bajo, Asier; De la Peña Esteban, Iñaki; Trigo-Martínez, Eduardo (MDPI, 2022)
In recent years, there has been a change in the main regulations governing the solvency of the world’s main insurance markets. Sustainability is an issue that is becoming increasingly important among to the various stakeholders in the insurance industry. It is a complex concept that has many different dimensions that can be included in these regulations, allowing for a more sustainable solvency. The paper uses a qualitative model previously designed and tested in the literature to analyse the solvency regulations of the European Union, United States of America, China, Australia, Brazil and South Africa and determine their level of convergence. It also links the criteria set out in these models to the dimensions of sustainability in order to determine the degree of sustainability of solvency systems and the questions that regulators will need to consider in the near future in order to achieve more sustainable solvency.
Keywords: Seguros; insurance sustainability; insurance supervision; risk management; capital requirements; solvency